Phosphorylation of AKT(Ser473) serves as an independent prognostic marker for radiosensitivity in advanced head and neck squamous cell carcinoma - Freudlsperger, Christian; Horn, Dominik; Weißfuß, Sebastian; Weichert, Wilko; Weber, Klaus-Josef; Saure, Daniel; Sharma, Sarika; Dyckhoff, Gerhard; Grabe, Niels; Plinkert, Peter K.; Hoffmann, Jürgen; Freier, Kolja; et al. (International journal of cancer, 2015)
Head and neck squamous cell carcinoma (HNSCC) is frequently characterized by high resistance to radiotherapy, which critically depends on both altered signaling pathways within tumor cells and their dynamic interaction with the tumor microenvironment. This study evaluated the prognostic value of the phosphorylation status of AKT on Ser473 and Thr308 for the clinical outcome of patients with advanced HNSCC on radiotherapy. Furthermore, we investigated the impact of AKT(Ser473) phosphorylation [p-AKT(Ser473)] in the context of radioresistance using ex vivo tissue cultures that resemble the complex tissue architecture and paracrine interaction with the tumor microenvironment. In a cohort of 120 patients with advanced HNSCC, who were treated with primary or adjuvant radiotherapy, a significant association was found between relative p-AKT(Ser473) levels and overall survival (p = 0.006) as well as progression-free survival (p = 0.021), while no significant correlation was revealed for relative p-AKT(Thr308) levels. In ex vivo tissue cultures p-AKT(Ser473) levels were increased upon irradiation and treatment with the PI3K inhibitor LY294002 inhibited both basal and irradiation induced AKT(Ser473) phosphorylation. Strikingly, pretreatment with LY294002 sensitized tissue cultures derived from primary and recurrent tumors to radiotherapy as determined by impaired tumor cell proliferation and enhanced DNA damage. In conclusion, phosphorylation status of AKT(Ser473) in tumor specimens serves as a novel biomarker to identify patients with advanced HNSCC at high risk for treatment failure following radiotherapy, and our data from ex vivo tissue cultures support the assumption that pharmacological inhibition of AKT(Ser473) phosphorylation might circumvent radioresistance to improve efficiency and reduce toxicity of current treatment modalities.